Does Parental Relational Aggression Interact with Parental Psychological Control in the Prediction of Youth Relational Aggression?. Issue 8 (2nd August 2016) - Lau, Katherine S. L.; Marsee, Monica A.; Lapré, Genevieve E.; Halmos, Miklos B.
ABSTRACT: In a sample of 117 youth and their parents, the associations between parental relational aggression, psychological control, youth gender, and youth relational aggression were examined. Boys with parents high on relational aggression and psychological control reported more relational aggression than boys with parents high on relational aggression and low on psychological control. Girls with parents low on relational aggression and high on psychological control reported more relational aggression than girls with parents low on relational aggression and psychological control. Results indicate youth may learn to use relational aggression from their parents, and have implications for intervention with relationally aggressive youth.